Novel peptide-based oncolytic vaccine for enhancement of adaptive antitumor immune response via co-engagement of innate Fcγ and Fcα receptors - Sari Pesonen; Sara Feola; Manlio Fusciello; Vincenzo Cerullo; Firas Hamdan; Jacopo Chiaro; Michaela Feodoroff; Gabriella Antignani; Salvatore Russo; Jeanette Leusen; Mikaela Grönholm; Federica D'Alessio; et al. (Journal for ImmunoTherapy of Cancer)
Background Cancer immunotherapy relies on using the immune system to recognize and eradicate cancer cells. Adaptive immunity, which consists of mainly antigen-specific cytotoxic T cells, plays a pivotal role in controlling cancer progression. However, innate immunity is a necessary component of the cancer immune response to support an immunomodulatory state, enabling T-cell immunosurveillance.Methods Here, we elucidated and exploited innate immune cells to sustain the generation of antigen-specific T cells on the use of our cancer vaccine platform. We explored a previously developed oncolytic adenovirus (AdCab) encoding for a PD-L1 (Programmed-Death Ligand 1) checkpoint inhibitor, which consists of a PD-1 (Programmed Cell Death Protein 1) ectodomain fused to an IgG/A cross-hybrid Fc. We coated AdCab with major histocompatibility complex (MHC-I)-restricted tumor peptides, generating a vaccine platform (named PeptiCab); the latter takes advantage of viral immunogenicity, peptide cancer specificity to prime T-cell responses, and antibody-mediated effector functions.Results As proof of concept, PeptiCab was used in murine models of melanoma and colon cancer, resulting in tumor growth control and generation of systemic T-cell-mediated antitumor responses. In specific, PeptiCab was able to generate antitumor T effector memory cells able to secrete various inflammatory cytokines. Moreover, PeptiCab was able to polarize neutrophils to attain an antigen-presenting phenotype by upregulating MHC-II, CD80 and CD86 resulting in an enhanced T-cell expansion.Conclusion Our data suggest that exploiting innate immunity activates T-cell antitumor responses, enhancing the efficiency of a vaccine platform based on oncolytic adenovirus coated with MHC-I-restricted tumor peptides.